2018
DOI: 10.1111/jeu.12631
|View full text |Cite
|
Sign up to set email alerts
|

The 14th International Workshops on Opportunistic Protists (IWOP 14)

Abstract: The 14th International Workshops on Opportunistic Protists (IWOP-14) was held August 10-12, 2017 in Cincinnati, OH, USA. The IWOP meetings focus on opportunistic protists (OIs); for example, free-living amoebae, Pneumocystis spp., Cryptosporidium spp., Toxoplasma, the Microsporidia, and kinetoplastid flagellates. The highlights of Pneumocystis spp. research included the reports of primary homothallism for mating; a potential requirement for sexual replication in its life cycle; a new antigen on the surface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Taken together, our findings indicate that this entity has distinct clinical and immunologic features, clearly distinguishable from other disorders including known causes of PAP, and represents an uncharacterized inflammatory ILD. Some of the patients and results of these studies have been previously reported .…”
Section: Introductionmentioning
confidence: 97%
“…Taken together, our findings indicate that this entity has distinct clinical and immunologic features, clearly distinguishable from other disorders including known causes of PAP, and represents an uncharacterized inflammatory ILD. Some of the patients and results of these studies have been previously reported .…”
Section: Introductionmentioning
confidence: 97%
“…Cryptosporidiosis has increasingly been recognized as an alarming global health problem. In the United States alone, 750,000 cases of cryptosporidiosis have been reported to occur annually (10). Stunted growth and associated high mortality and morbidity have also been reported in two recent multicenter studies [The Global Enteric Multicenter Study (GEMS) (21) and a global network study of malnutrition and enteric diseases (MAL-ED) (27)] that recognized this neglected parasite as one of the four major diarrheal pathogens in infants.…”
Section: Introductionmentioning
confidence: 99%